Law and political economy in China : the role of law in corporate governance and market growth / Tamar Groswald Ozery. - Groswald Ozery, Tamar (ASCL studies in comparative law., 2023)
Applying a novel theoretical approach, Tamar Groswald Ozery combines law and political economy to deconstruct the role of law in China's market development since 1978. With a vast range of primary sources, Ozery examines the complex, entwined relationships between law, politics and economics to explain corporate development and governance in China.